Basal melt and strain rates derived from phase-sensitive radars (ApRES) at Nivlisen ice shelf, East Antarctica - Lindbäck, Katrin (Norwegian Polar Institute, 2019)
The dataset consists of basal melt and strain rates derived from phase-sensitive radars (ApRES) on Nivlisen ice shelf, Dronning Maud Land (70 deg S, 12 deg E). If you use the dataset in presentations and publications please also refer to to the peer-reviewed paper (Lindbäck et al., 2019, https://doi.org/10.5194/tc-2019-108), where the data is described in more detail. The dataset will be updated when the quality of the data is improved or if new datasets become available. File format: Text file Contact person: Kenichi Matsuoka (kenichi.matsuoka@npolar.no) This work was part of the MADICE (Mass balance, dynamics, and climate of the central Dronning Maud Land coast, East Antarctica) project co-led by the Norwegian Polar Institute in Norway and National Centre for Polar and Ocean Research in India (https://www.npolar.no/prosjekter/madice/).